2018
DOI: 10.1039/c8tx00058a
|View full text |Cite
|
Sign up to set email alerts
|

Genoprotective effects of gallic acid against cisplatin induced genotoxicity in bone marrow cells of mice

Abstract: Gallic acid is a natural polyhydroxy-phenolic compound. The objective of this study is to evaluate the protective effects of gallic acid against chemotherapeutic drug cisplatin induced damage in bone marrow cells of mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The flavonoids, catechins, and their derivatives have been considered as neuroprotective agents 16 . Our previous study confirmed the antimutagenic potential of GA against cisplatin induced genotoxicity in mice bone marrow cells 17 . Further our study gave some insight on immunostimulatory effect of GA against CP and cisplatin induced immunosuppression in Swiss albino mice 18 .…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The flavonoids, catechins, and their derivatives have been considered as neuroprotective agents 16 . Our previous study confirmed the antimutagenic potential of GA against cisplatin induced genotoxicity in mice bone marrow cells 17 . Further our study gave some insight on immunostimulatory effect of GA against CP and cisplatin induced immunosuppression in Swiss albino mice 18 .…”
Section: Introductionsupporting
confidence: 69%
“…16 Our previous study confirmed the antimutagenic potential of GA against cisplatin induced genotoxicity in mice bone marrow cells. 17 Further our study gave some insight on immunostimulatory effect of GA against CP and cisplatin induced immunosuppression in Swiss albino mice. 18 These findings incited us to evaluate possible anticlastogenic, antigenotoxic, and antioxidant effects of GA against CP induced oxidative damage in Swiss albino mice.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, we and others have shown that the use of natural molecules such as polyphenols can modulate xenobiotic-metabolizing enzymes as well as the pathways leading to cancer cell death, making it possible to restore sensitization to anticancer agents. For example, resveratrol, curcumin, vitamin E, and gallic acid are able to protect cells from cisplatin-induced genotoxicity [13][14][15]. Very interestingly, some of these natural compounds are able to synergize at the same time with various anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 To minimize cisplatin-mediated toxicities and resistance, several combination treatments have been used, wherein two or more drugs/agents with different pharmacological properties are often used. [9][10][11] Flavonoids or bioflavonoids are a category of secondary metabolites of plants and fungal origin. Flavonoids possess a wide range of important biological and pharmacological activities which could be very helpful in promoting human health.…”
Section: Introductionmentioning
confidence: 99%